2022
DOI: 10.1186/s12890-021-01809-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis and nomogram for predicting in-hospital mortality in ICU patients with sepsis and lung infection

Abstract: Background Lung infection is a common cause of sepsis, and patients with sepsis and lung infection are more ill and have a higher mortality rate than sepsis patients without lung infection. We constructed a nomogram prediction model to accurately evaluate the prognosis of and provide treatment advice for patients with sepsis and lung infection. Methods Data were retrospectively extracted from the Medical Information Mart for Intensive Care (MIMIC-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 46 publications
7
31
0
1
Order By: Relevance
“…To date, several studies have identified a link between the respiratory rate and worse outcomes [ 25 ]. Additionally, we found that urine output was associated with better outcomes, which was consistent with those of previous studies [ 26 ]. In the present study, age was shown to be a predictor of mortality in critically ill patients with sepsis.…”
Section: Discussionsupporting
confidence: 92%
“…To date, several studies have identified a link between the respiratory rate and worse outcomes [ 25 ]. Additionally, we found that urine output was associated with better outcomes, which was consistent with those of previous studies [ 26 ]. In the present study, age was shown to be a predictor of mortality in critically ill patients with sepsis.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have shown that NLR, PLR are inflammatory indicators, independent risk factors and prognostic predictors of sepsis, which is consistent with our findings [ 23 , 24 , 25 , 26 , 27 ]. Also, Platelets have also been shown to be associated with the severity and prognosis of sepsis [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the one hand, surviving patients have better renal function than patients in the dead group according to the comparison of CrCl, which is related to a lower demand on CRRT. On the other hand, some clinical studies indicate that CRRT might not be beneficial to effectively lower mortality for infected patients or those with sepsis [26,27].…”
Section: Discussionmentioning
confidence: 99%